2020
DOI: 10.3390/polym12030658
|View full text |Cite
|
Sign up to set email alerts
|

Nano- And Microfiber-Based Fully Fabric Triboelectric Nanogenerator For Wearable Devices

Abstract: The combination of the triboelectric effect and static electricity as a triboelectric nanogenerator (TENG) has been extensively studied. TENGs using nanofibers have advantages such as high surface roughness, porous structure, and ease of production by electrospinning; however, their shortcomings include high-cost, limited yield, and poor mechanical properties. Microfibers are produced on mass scale at low cost; they are solvent-free, their thickness can be easily controlled, and they have relatively better mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…As of now, within the biomedical field, TENG‐generated electricity has been utilized to power wearable devices, enable the sensing of physiological functions such as heart rate, and treat various diseases and conditions through therapeutic ES. [ 124–136 ] There are many different types of TENG working modes including vertical contact separation, [ 137,138 ] in‐plane sliding, [ 139,140 ] single electrode, [ 141–144 ] and freestanding, [ 145–148 ] which give further leeway to utilizing TENG devices for IOB therapeutic applications due to the ability of TENG devices to harness electricity from a wide variety of biomechanical motions. TENGs’ versatility renders them optimal self‐powered biomedical sensors, [ 149–155 ] providing sensing insight via means of signal‐to‐function association.…”
Section: Introductionmentioning
confidence: 99%
“…As of now, within the biomedical field, TENG‐generated electricity has been utilized to power wearable devices, enable the sensing of physiological functions such as heart rate, and treat various diseases and conditions through therapeutic ES. [ 124–136 ] There are many different types of TENG working modes including vertical contact separation, [ 137,138 ] in‐plane sliding, [ 139,140 ] single electrode, [ 141–144 ] and freestanding, [ 145–148 ] which give further leeway to utilizing TENG devices for IOB therapeutic applications due to the ability of TENG devices to harness electricity from a wide variety of biomechanical motions. TENGs’ versatility renders them optimal self‐powered biomedical sensors, [ 149–155 ] providing sensing insight via means of signal‐to‐function association.…”
Section: Introductionmentioning
confidence: 99%
“…Greater conformity with the countersurface is likely to generate increased contact area. The higher dielectric constant and contact area can confer enhanced electrical performance for nanofiber-based TENGs. , However, electrospun nanofibers do have lower mechanical properties as compared to microfibers. , Therefore, we deposit the electrospun layer onto a conventional woven fabric to provide the required mechanical strength and stability. In this work, nylon 66 electrospun nanofibers are deposited on a silk woven fabric to form the tribo-positive layer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45,54,55 ] Quite recently, few reports emerged to focus on meltblown nonwoven fabrics, highlighting the relationship between structural features and their energy‐generating capabilities. [ 56–58 ] Meltblown nonwoven refers to a group of nonwoven fabrics produced by melt‐blowing process, which is a conventional one‐step nonwoven production technique. [ 59 ] This solvent‐free process is able to provide cost‐effective and high‐quality tribolayers in different chemical compositions and with relatively good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The open‐circuit voltage ( V OC ) is enhanced from 1.55 to 3.54 V when basis weight of PP meltblown nonwoven increases from 15 to 50 g m −2 . [ 56 ] Peng et al. reported that the triboelectric output ( V OC ) carries a maximum at a specific basis weight of PP nonwoven.…”
Section: Introductionmentioning
confidence: 99%